(untitled) (Eurasian Journal of Philology Science and Education, 2015)
The article describes the usage of reiterations in short cautionary tales provided in collection named “Gibratnama” of Qadir Mirza Ali. The author uses various methods in order to expressively effect on the reader, reiteration is one of them. The main point of the article is the term "reiteration" and its establishment as a term and stylistic category in Kazakh linguistics. Based on short cautionary tales the following types of reiteration were disclosed: contact and distant, enclosing and butting. Their functions in the text are proved by the examples. The ability of using the reiteration in right position and advantage aiming to enhance the stylistic emotional colouring of the text shows the absolute mastery of writer.